2010
DOI: 10.3814/2010/395215
|View full text |Cite
|
Sign up to set email alerts
|

The Utility of Rapid Microbiological and Molecular Techniques in Optimizing Antimicrobial Therapy

Abstract: Early treatment of bloodstream infections with appropriate, definitive antimicrobial therapy has proven to reduce mortality, length of hospital stay, and healthcare costs. Culture-based testing methods require up to five days for final pathogen identification and susceptibility reporting, forcing use of broad spectrum empiric therapy. Recently, multiple rapid microbiological and molecular testing methods have been developed that reduce the time to identify the pathogen and susceptibility, allowing optimal anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Study performed by Eiland III et al showed similar results. 22 For the prevention of development of resistance antimicrobial stewardship programme should be initiated in the hospital and guidelines should be formulated for effective use of antimicrobials at hospital. Antimicrobial stewardship programme have been shown to reduce inappropriate antimicrobial use, with resulting reductions in antimicrobial resistance, and also lead to more appropriate antimicrobial therapy for infections where therapy is required, with improved clinical outcomes for patients.…”
Section: Discussionmentioning
confidence: 99%
“…Study performed by Eiland III et al showed similar results. 22 For the prevention of development of resistance antimicrobial stewardship programme should be initiated in the hospital and guidelines should be formulated for effective use of antimicrobials at hospital. Antimicrobial stewardship programme have been shown to reduce inappropriate antimicrobial use, with resulting reductions in antimicrobial resistance, and also lead to more appropriate antimicrobial therapy for infections where therapy is required, with improved clinical outcomes for patients.…”
Section: Discussionmentioning
confidence: 99%
“…Collectively, these benefits may positively impact technologist safety, workflow, costs, and throughput compared to other FDA-cleared molecular platforms and direct detection blood culture assays. Most importantly, the use of direct detection molecular blood culture assays, such as the iC-GPC Assay, will significantly reduce morbidity and mortality rates, shorten hospital stays, decrease costs, and favorably impact hospital antibiotic stewardship programs ( 25 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies of RMPT for septicemia have also demonstrated both cost savings and survival benefits [31,32]. The test with the most extensive evidence of cost savings is PNA FISH (peptide nucleic acid fluorescent in situ hybridization), one of the earliest molecular methods used in rapid pathogen identification and one of the easiest to implement.…”
Section: Other Studiesmentioning
confidence: 99%